A molecular screening assay to identify Chlamydia trachomatis and distinguish new variants of C. trachomatis from wild‐type. Issue 2 (5th December 2020) - Xiu, Leshan; Li, Yamei; Zhang, Chi; Li, Yizhun; Zeng, Yaling; Wang, Feng; Peng, Junping
Summary: Chlamydia trachomatis is the most common sexually transmitted pathogen globally, causing serious health problems and representing a burden on public health. A new variant of C. trachomatis (nvCT) that carries mutations (C1514T, C1515T and G1523A) in the 23S rRNA gene has eluded detection in Aptima Combo 2 assays. This has led to false negatives in diagnostics tests and poses a challenge for C. trachomatis diagnostics on a global level. In this study, we developed a simple and cost‐effective assay to identify C. trachomatis, with a potential application to screen for nvCT. We developed a screening assay based on high‐resolution melting (HRM), targeting the 23S rRNA gene and cryptic plasmid. To evaluate the performance of the assay, 404 archived C. trachomatis DNA specimens and 570 extracted clinical specimens were analysed. Our HRM assay not only identified C. trachomatis in clinical specimens, but also correctly differentiated nvCT carrying C1514T, C1515T and G1523A mutations from the wild‐type. We observed no cross‐reactions with other clinically related agents, and the limit of detection was 11.26 (95% CI; 7.61–31.82) copies per reaction. Implementation of this screening assay could reduce detection times and costs for C. trachomatis diagnoses, and facilitate increased research on the presence and monitoring of nvCT. Abstract : Since timely determination of nvCT is critical for restricting further infection spread in the population, we have developed a screening assay based on high‐resolution melting (HRM) that can detect C. trachomatis and identify nvCT. Our results showed that the HRM scanning assay is not only able to directly identify C. trachomatis in clinical specimens, but also to correctly differentiate nvCT with mutation C1514T, C1515T and G1523A from the wild‐type.